THE INTERTWINED ROLES OF SELF-EFFICACY AND CAREER READINESS IN FINAL YEAR STUDENTS - Iis Maisaroh; Sandi Pradana (Indonesian Journal of Education and Youth Development, 2025)
The transition from higher education to the professional world presents a significant challenge for final-year students. One crucial factor contributing to career readiness is self-efficacy, which refers to an individual's belief in their ability to perform specific tasks. This study reviews the relationship between self-efficacy and career readiness based on existing literature. The analysis reveals that students with higher levels of self-efficacy demonstrate greater career readiness, increased confidence in career decision-making, and a more proactive approach to exploring job opportunities. These findings emphasize the importance of strengthening self-efficacy through higher education and career counseling services to enhance students’ preparedness for entering the workforce.